Rare earth and transition metal doping of semiconductor materials : synthesis, magnetic properties and room temperature spintronics - Dierolf, Volkmar, 1960-; Ferguson, Ian T.; Zavada, J. M. (Woodhead Publishing series in electronic and optical materials ;, 2016)
Rare Earth and Transition Metal Doping of Semiconductor Material explores traditional semiconductor devices that are based on control of the electron electric charge. This book looks at the semiconductor materials used for spintronics applications, in particular focusing on wide band-gap semiconductors doped with transition metals and rare earths. These materials are of particular commercial interest because their spin can be controlled at room temperature, a clear opposition to the most previous research on Gallium Arsenide, which allowed for control of spins at supercold temperatures. Part One of the book explains the theory of magnetism in semiconductors, while Part Two covers the growth of semiconductors for spintronics. Finally, Part Three looks at the characterization and properties of semiconductors for spintronics, with Part Four exploring the devices and the future direction of spintronics. Examines materials which are of commercial interest for producing smaller, faster, and more power-efficient computers and other devicesAnalyzes the theory behind magnetism in semiconductors and the growth of semiconductors for spintronicsDetails the properties of semiconductors for spintronics.